Makna Persahabatan Bagi Mahasiswa Rantau: Studi Kualitatif: Penelitian - Nova Lisye Sinaulan; Marssel M. Sengkey; Yoas Sotomo Telaumbanua; Imanuel Yohanis Kountul; Brian Watuseke (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Inter-students face unique challenges in the process of social and emotional adaptation due to living far from their families and home environment. In this context, friendship becomes an important element that not only functions as a social network, but also as a deep psychological support system. This study aims to uncover the meaning of friendship for inter-students through a qualitative approach with a phenomenological method. A total of 10 participants who were inter-students were interviewed in depth using a semi-structured format. Data analysis was conducted using the thematic analysis method which resulted in five main themes: (1) friendship as emotional support, (2) friendship as a substitute family, (3) friendship as a coping mechanism in academic and social pressures, (4) friendship as a safe space for self-expression, and (5) conflict dynamics as a relationship strengthener. The results of the study indicate that friendship has a complex and multifunctional meaning, covering emotional, social, and existential dimensions. Friendship relationships have been shown to contribute to maintaining students' psychological stability, strengthening academic resilience, and forming self-identity in a new environment. These findings emphasize the importance of building a strong social support system for inter-students, both through institutional interventions and community approaches. This study also opens up opportunities to study further the factors that influence the dynamics of social relationships in the context of students' life transitions.